Armies of Ancient Persia: The Sassanians. - Farrokh, Kaveh (Pen and Sword, 2014)
Throughout most of the classical period, Persia was one of the great superpowers, placing a limit on the expansion of Western powers. It was the most formidable rival to the Roman empire for centuries, until Persia, by then under the Sassanians, was overwhelmed by the Islamic conquests in the seventh century AD. Yet, the armies of ancient Persia have received relatively little detailed attention, certainly in comparison to those of Rome. This work is the firsst of three volumes that will form the most comprehensive study of ancient Persian armies available. The Sassanians, the native Iranian dynasty that ousted their Parthian overlords in AD 226, developed a highly sophisticated army that was able for centuries to hold off all comers. They continued the Parthians famous winning combination of swift horse archers with heavily-armored cataphract cavalry, also making much use of war elephants, but Kaveh Farrokh interestingly demonstrates that their oft-maligned infantry has been much underestimated. The author, born in Athens, Greece, and expert in ancient Persian languages and military history, has been researching the military history and technology of Persia for a quarter of a century. He draws on the latest research and new archaeological evidence, focusing on the organization, equipment and tactics of the armies that dominated the ancient Middle East for so long.